Impact of salt stress on physiological traits in tomato (Lycopersicon esculentum Mill.) - Kumar, M; Vanitha, K; Sankari, A (Plant Science Today, 2025)
Salt stress is a major abiotic factor that limits plant growth and development globally, primarily due to the use of low-quality irrigation water and soil salinization caused by seawater intrusion. This study examines physiological parameters, antioxidant enzymes and the K/Na ratio in response to salt stress in various tomato genotypes at a salinity level of 8 dS m-1 during the vegetative stage. Specifically, it investigates superoxide dismutase activity, relative water content, electrolyte leakage, proline content, chlorophyll fluorescence and potassium and sodium ion content in roots, shoots and leaves. The results revealed significant variation in salt tolerance among the different genotypes. Genotypes LE-14 and LE-1 demonstrated superior performance under salt stress, displaying higher relative water content, reduced electrolyte leakage, increased superoxide dismutase activity, elevated proline content and favorable K/Na ratios. Principal component analysis showed significant eigenvalues, accounting for 72.5% of the total variability. These findings provide valuable insights into the mechanisms of salt tolerance in tomato crops and highlight the potential of LE-14 and LE-1 for cultivation in saline environments. The study emphasizes the importance of conducting field trials to validate these results for sustainable production in saltaffected areas.